Interaction of industrially relevant cationic starches with cellulose. (1st January 2018) - Niegelhell, Katrin; Chemelli, Angela; Hobisch, Josefine; Griesser, Thomas; Reiter, Heidemarie; Hirn, Ulrich; Spirk, Stefan
Highlights: The adsorption of cationic starches onto cellulose was investigated in real-time. All cationic starches adsorbed irreversibly onto cellulose thin films. The adsorption behavior was linked to intrinsic properties of the cationic starches. Abstract: Industrially relevant, commercially available cationic starches have been investigated towards their interaction capacity with cellulose thin films derived from trimethylsilyl cellulose (TMSC). The starches used in this study stem from different sources (potato, pea, corn) and featured rather low degrees of substitution ranging from 0.030 to 0.062. The interaction of those starches with cellulose thin films was studied by surface plasmon resonance spectroscopy under flow conditions using concentrations of 1.0 mg ml −1 and a flow rate of 25 μl min −1 . All the investigated starches employed in this study were capable to efficiently interact with the slightly negatively charged cellulose surface leading to irreversible deposition on the surface. As complementary techniques atomic force microscopy and x-ray photoelectron spectroscopy were used to confirm the presence of the starches on the cellulose film surface. Further, dynamic light scattering and size exclusion chromatography measurements were performed to correlate adsorbed amount, particle size and molecular weight of the starches to their interaction behavior.